Metabolomic profiling and anti-infective potential of Zinnia elegans and Gazania rigens (Family Asteraceae). Issue 18 (16th September 2020) - Gomaa, Alshymaa Abdel-Rahman; Samy, Mamdouh Nabil; Abdelmohsen, Usama Ramadan; Krischke, Markus; Mueller, Martin J.; Wanas, Amira Samir; Desoukey, Samar Yehia; Kamel, Mohamed Salah
Abstract: The present study evaluates the chemical composition of Zinnia elegans and Gazania rigens based on their metabolomic profiles using liquid chromatography coupled with high-resolution mass spectrometry (LC‐HR-MS), alongside with the anti-infective activities of their ethanol extracts, as well as, different fractions. A significant difference was observed between the LC-MS profiles of the two plants such as, coumarins, sesquiterpene lactones and phenylethanoids which were characteristic for Z. elegans, while amides and phenolic acid derivatives were characteristic for G. rigens . These results highlight the chemical potential of Z. elegans and G. rigens. Furthermore, the ethyl acetate fraction of Z. elegans showed a significant antimalarial activity with IC50 values of 21.03 and 13.72 µg/mL against Plasmodium falciparum D6 and P. falciparum W2, respectively. Graphical Abstract: